HUBUNGAN KARAKTERISTIK PETERNAK TERHADAP PRODUKSI SAPI BALI DI DESA BERORA KECAMATAN LOPOK - Aditya Wira Saputra, Banu; Yani, Ahmad; Sudirman, Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between farmer characteristics and Bali cattle production in Berora Village. The variables studied were the independent variables (farmer age, education level, and farming experience). The dependent variable was Bali cattle production. This study used a quantitative method with a direct survey and purposive sampling technique to determine the research location in Berora Village. A random sampling technique was used to select 66 respondents. Data collection involved questionnaires, interviews, and observations. Pearson correlation analysis was used to analyze the data. The results showed that the relationship between farmer age, education level, and farming experience was quite strong, highly significant (P<0.05), and positive.